2014
DOI: 10.1021/jf5051848
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Phenolic Extracts from “Sugarbag” Pot-Honeys of Australian Stingless Bees (Tetragonula carbonaria)

Abstract: Australian stingless bee honeys have been shown to exert antioxidant and in vitro antimicrobial properties; however their bioactive factors remained unidentified. This study investigated the antibacterial properties of phenolic extracts from Tetragonula carbonaria honeys. Honeys were harvested from beehives in three sites of South East Australia. Liquid-liquid extractions yielded the phenolic concentrates, for analyses by liquid and gas chromatography mass spectrometry. Antibacterial assays were conducted agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…Other honey components, such as phenolic compounds originating from plant nectar or, in HD honeys, from excretions of plant-sucking insects, have been proposed as possible antibacterial agents. Several phenolics have so far been identified in honeys, including caffeic, p-coumaric and ellagic acids (Escuredo et al, 2012), diglycosyl flavonoids and terpenes (Massaro et al, 2014). While most of them have antibacterial activity, their contribution to the antibacterial properties of honey is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Other honey components, such as phenolic compounds originating from plant nectar or, in HD honeys, from excretions of plant-sucking insects, have been proposed as possible antibacterial agents. Several phenolics have so far been identified in honeys, including caffeic, p-coumaric and ellagic acids (Escuredo et al, 2012), diglycosyl flavonoids and terpenes (Massaro et al, 2014). While most of them have antibacterial activity, their contribution to the antibacterial properties of honey is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity studies of stingless bee honey broad spectrum antibacterial activity because honey can act against a wide range of bacteria that able to cause disease (Boorn et al, 2010;. Most of the studies of honey were performed on Staphylococcus aureus (Miorin et al, 2003;Demera et al, 2004;Temaru et al, 2007;Chanchao et al, 2009;Boorn et al, 2010;Chan-Rodriguez et al, 2012;Ilechie et al, 2012;Andualem et al, 2013;Ewnetu et al, 2013;Merces et al, 2013;Queiroz et al, 2013;Zainol et al, 2013;Nobre da Cruz et al, 2014;Massaro et al, 2014;Zamora et al, 2014) showed that it is the most susceptible tested pathogen to stingless bee honey. As we know, Staphylococcus aureus is a common pathogen found in human skin and can cause infection in the presence of a wound.…”
Section: Trigona Incisa Trigona Apicalis T Fuscobalteata T Fuscimentioning
confidence: 99%
“…Previous study showed that stingless bee honey can act as anti-inflammatory (Borsato et al, 2014), anticancer (Kustiawan et al, 2014;Yazan et al, 2016), antimicrobial (Miorin et al, 2003;Demera et al, 2004;Garedew et al, 2004;Temaru et al, 2007;Kimoto-Nira and Amano, 2008;Chanchao et al, 2009;Boorn et al, 2010;Rodríguez et al, 2012;Ilechie et al, 2012;Andualem, 2013;Ewnetu et al, 2013;Mercês et al, 2013;Queiroz et al, 2013;Zainol et al, 2013;Nobre da Cruz et al, 2014;Massaro et al, 2014;Zamora et al, 2014;Medeiros et al, 2016;De Sousa et al, 2016; and possessed antioxidant properties (Duarte et al, 2012;Almeida da Silva et al, 2013;De Sousa et al, 2016). However, the beneficial of stingless bee honey has been abandoned in modern medicine due to the paucity of systematic scientific studies for supporting its medical properties (Pe´rez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, compounds1,4,5,8,12,13,22,27,33,34,38,39, 49, 51 and 53 were shown to have antibacterial properties against Gram-positive and Gram-negative bacteria including Mycobacterium smegmatis, M. avium, Micrococcus luteus, Enterococcus faecalis, S. aureus and S. epidermidis, E. faecium, B. subtilis, P. aeruginosa, E. coli, P. reinekei and H. pylori. Compounds 3, 16 and 39 were shown to possess anti-inflammatory activity[14][15][16][17][18][19][20][21][22].Compounds 11,13,36,39, 48 and 54 possess antifungal activity where compounds 15 and 16 possess anti-oxidant activities[23][24][25][26][27]. Moreover, there was no biological activity reported for compounds2, 3, 7, 9, 26, 28, 29, 40, 42 and 47.…”
mentioning
confidence: 99%